Experience of Using the Antiviral Therapy of Generalized Congenital Cytomegalovirus Infection - G. V. Petrova; V. I. Shakhgildyan; E. A. Chistozvonova; T. A. Pugacheva; N. V. Turkot; M. V. Egorova; O. U. Sautenko; I. B. Astasheva; O. V. Romanova; N. V. Kostycheva; T. A. Grigorieva; M. G. Kulagina (LLC "Diagnostics and Vaccines", 2016)
The article presents the results of observation and treatment with ganciclovir and oral valganciclovir form of a premature infant with congenital generalized symptomatic cytomegalovirus infection (CMVI) involving pathology of CNS, cholangitis, spontaneous pathologic fracture of femoral bone. When using ganciclovir and valganciclovir demonstrated gradual normalization of clinical and hematological parameters. In the course of treatment with ganciclovir and valganciclovir was not revealed any adverse reactions. While maintaining the CMV DNA in the blood, the duration of specific therapy, according to international recommendations, should be not less than 6 months. The decision to use a specific therapy should be made on the basis of the medical consultation, the conclusions of the medical commission and informed consent of the parents.